(untitled) (Journal of Environmental Microbiology and Toxicology, 2023)
Many organic and inorganic contaminants are present in wastewater, and releasing them into receiving waterways causes major environmental problems. The wastewater produced by numerous industries contains a significant amount of dyes; this continues to be one of the most serious ecological issues confronting public health. Unfortunately, conventional wastewater remediation methods are incapable of completely removing dyes. Biosorption is the process by which living material removes chemicals from a solution. Organic, inorganic, gaseous, liquid, or insoluble substances are examples of such substances. Absorption, adsorption, ion exchange, surface complexation, and precipitation are all mechanisms involved in this physicochemical process. It is a characteristic shared by both live and dead biomass. Triphenyl methane dyes are a significant category of commercial dyes known for their remarkable color intensity, bright red, green, and blue colors, and low lightfastness on many substrates. In contrast to live biomass, using dead biomass in biosorption is more ideal since the hazardous nature of pollutants does not affect the sorption process. There is also no need to provide nutrients or maintain a growing environment. In addition to these variables, researchers discovered that dead biomass is more efficient than active biomass at absorbing organic contaminants. This review highlighted the toxicity of dyes, principles, and theory of the adsorption process, isotherm and kinetic studies of some microbial biosorbents, and thermodynamic studies of triphenyl methane dyes adsorption.